The Romanian Youth’s Contact with the West in the 19th Century: Education, Connections and Political Formation - Cosmin-Ștefan, Dogaru (European Scientific Journal, ESJ, 2018)
In the 19th century, Western Europe became a landmark for the future Romanian leaders, and the developed West European countries constituted a model to be followed in terms of state organization. From this point of view, the young Romanians who studied in various cultural and political milieus, such as the French or the German etc., were influenced by the societies of the respective countries, acquiring a scientific knowledge and forming an intellectual and political thinking which was distinct from that of their parents. When they returned home, with a new mentality and with desire for modernisation, many of these young people became involved in the political life, militating for the organization of the state on the basis of the European model, adopting reforms on all levels: social, political, economic and cultural.